Environmental factors influence somatic cell reprogramming to cardiomyocyte-like cells. (February 2022) - Van Handel, Ben; Wang, Lingjun; Ardehali, Reza
Abstract: Direct cardiac reprogramming, which refers to somatic cell ( i.e . fibroblast) fate conversion to cardiomyocyte-like cell without transitioning through an intermediate pluripotent state, provides a novel therapeutic strategy for heart regeneration by converting resident cardiac fibroblasts to cardiomyocytes in situ . However, several limitations need to be addressed prior to clinical translation of this technology. They include low efficiency of reprogramming, heterogeneity of starting fibroblasts, functional immaturity of induced cardiomyocytes (iCMs), virus immunogenicity and toxicity, incomplete understanding of changes in the epigenetic landscape as fibroblasts undergo reprogramming, and the environmental factors that influence fate conversion. Several studies have demonstrated that a combination of enforced expression of cardiac transcription factors along with certain cytokines and growth factors in the presence of favorable environmental cues (including extracellular matrix, topography, and mechanical properties) enhance the efficiency and quality of direct reprogramming. This paper reviews the literature on the influence of the microenvironment on direct cardiac reprogramming in vitro and in vivo .